2004
DOI: 10.1093/brain/awh132
|View full text |Cite
|
Sign up to set email alerts
|

Cortical selective vulnerability in motor neuron disease: a morphometric study

Abstract: Neuroimaging and neuropsychological studies have revealed that the primary motor cortex (PMC) and the extramotor cortical areas are functionally abnormal in motor neuron disease (MND, amyotrophic lateral sclerosis), but the nature of the cortical lesions that underlie these changes is poorly understood. In particular, there have been few attempts to quantify neuronal loss in the PMC and in other cortical areas in MND. We used SMI-32, an antibody against an epitope on non-phosphorylated neurofilament heavy chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 95 publications
8
90
0
2
Order By: Relevance
“…Together with reports of interneuronal loss in spinal cord and cortex of human ALS patients (Maekawa et al, 2004;Stephens et al, 2006) and in transgenic mice overexpressing mutant hSOD1 (Morrison et al, 1998), this suggests that early hyperexcitability in interneurons may also contribute to interneuronal loss at later stages in ALS.…”
Section: G93a Motoneurons and Interneurons As In Fals Patients Hsod1supporting
confidence: 63%
“…Together with reports of interneuronal loss in spinal cord and cortex of human ALS patients (Maekawa et al, 2004;Stephens et al, 2006) and in transgenic mice overexpressing mutant hSOD1 (Morrison et al, 1998), this suggests that early hyperexcitability in interneurons may also contribute to interneuronal loss at later stages in ALS.…”
Section: G93a Motoneurons and Interneurons As In Fals Patients Hsod1supporting
confidence: 63%
“…The cognitively impaired patients also had UIBs in the temporal, occipital, and entorhinal cortices, posterior cingulate gyrus, caudate, and putamen. Computerized morphometry revealed a 25% reduction in the pyramidal neuronal density in layer V of the premotor cortex, dorsolateral prefrontal cortex, and anterior cingulate cortex compared with age-matched controls (Maekawa et al, 2004). This is particularly relevant in the context of findings from positron emission tomography neuroimaging which identified decreased binding of the GABAergic ligand (11C)-flumazenil in the prefrontal cortex (Lloyd et al, 2000;Turner et al, 2005) and increased microglial activation (implicated in mechanisms of neuronal cell death) in the dorsolateral prefrontal cortex (Turner et al, 2004).…”
Section: Cellular and Molecular Pathogenesis Of Alsmentioning
confidence: 78%
“…The major pathological features of ALS include: (1) degeneration of the corticospinal tracts and extensive loss of lower motoneurons or anterior horn cells (Garofalo et al, 1995;Ghatak et al, 1986;Hughes, 1982); (2) degeneration and loss of Betz cells and other pyramidal cells in the primary motor cortex (Hammer et al, 1979;Maekawa et al, 2004;Udaka et al, 1986); and (3) reactive gliosis in the motor cortex and spinal cord (Ekblom et al, 1994;Kawamata et al, 1992;Murayama et al, 1991;Schiffer et al, 1996).…”
Section: Cellular and Molecular Pathogenesis Of Alsmentioning
confidence: 99%
“…Pathological studies demonstrate a particular vulnerability of parvalbumin‐positive interneurons [Maekawa et al, 2004; Nihei et al, 1993], later shown to contribute to reduced inhibitory GABA‐ergic tone in animal models [McGown et al, 2013; Nieto‐Gonzalez et al, 2011]. Neuroimaging studies across multiple modalities have supported the concept of reduced cortical inhibition.…”
Section: Discussionmentioning
confidence: 99%